Desenvolvimento da automação, controle e supervisão de um sistema de ensaios de vazão e temperatura com tanques em desnível - Nassar, Gabriel (2017)
This project is the development of a didactic industrial plant with tanks in gap. And also the implementation of automation, control and supervision of the same, conducting tests of flow and temperature. It is used the ScadaBR software for the implementation of the supervisory system which contains a free license. In this way, the contents are related to industrial process control, programmable logic controllers and their languages and supervisory systems.